DNA Nanostructures for Rational Regulation of Cellular Organelles - Elblová, Petra; Anthi, Judita; Liu, Minghui; Lunova, Mariia; Jirsa, Milan; Stephanopoulos, Nicholas; Lunov, Oleg (JACS Au, 2025)
DNA nanotechnology has revolutionized materials science and biomedicine by enabling precise manipulation of matter at the nanoscale. DNA nanostructures (DNs) in particular represent a promising frontier for targeted therapeutics. Engineered DNs offer unprecedented molecular programmability, biocompatibility, and structural versatility, making them ideal candidates for advanced drug delivery, organelle regulation, and cellular function modulation. This Perspective explores the emerging role of DNs in modulating cellular behavior through organelle-targeted interventions. We highlight current advances in nuclear, mitochondrial, and lysosomal targeting, showcasing applications ranging from gene delivery to cancer therapeutics. For instance, DNs have enabled precision mitochondrial disruption in cancer cells, lysosomal pH modulation to enhance gene silencing, and nuclear delivery of gene-editing templates. While DNs hold immense promise for advancing nanomedicine, outstanding challenges include optimizing biological interactions and addressing safety concerns. This Perspective highlights the current potential of DNs for rational control of targeted organelles, which could lead to novel therapeutic strategies and advancement of precision nanomedicines in the future.